The Challenges of the Digital Transformation in Education Proceedings of the 21st International Conference on Interactive Collaborative Learning (ICL2018) - Volume 2 - Auer, Michael E.; Tsiatsos, Thrasyvoulos (Advances in Intelligent Systems and Computing,, 2019)
This book offers the latest research and new perspectives on Interactive Collaborative Learning and Engineering Pedagogy. We are currently witnessing a significant transformation in education, and in order to face today's real-world challenges, higher education has to find innovative ways to quickly respond to these new needs. Addressing these aspects was the chief aim of the 21st International Conference on Interactive Collaborative Learning (ICL2018), which was held on Kos Island, Greece from September 25 to 28, 2018. Since being founded in 1998, the conference has been devoted to new approaches in learning, with a special focus on collaborative learning. Today the ICL conferences offer a forum for exchanging information on relevant trends and research results, as well as sharing practical experiences in learning and engineering pedagogy. This book includes papers in the fields of: * New Learning Models and Applications * Pilot Projects: Applications * Project-based Learning * Real-world Experiences * Remote and Virtual Laboratories * Research in Engineering Pedagogy * Technical Teacher Training It will benefit a broad readership, including policymakers, educators, researchers in pedagogy and learning theory, school teachers, the learning industry, further education lecturers, etc.